FROM POSTS TO PATTERNS: A METRIC TO CHARACTERIZE DISCUSSION BOARD ACTIVITY IN ONLINE COURSES - Bliss, Catherine A.; Lawrence, Betty (Online Learning, 2009)
Asynchronous text based discussion boards are included in many online courses, however strategies to compare their use within and between courses, from a disciplinary standpoint, have not been well documented in the literature. The goal of this project was to develop a multi-factor metric which could be used to characterize discussion board use in a large data set (n=11,596 message posts) and to apply this metric to all Mathematics courses offered in the January 2008 term by the Center for Distance Learning at Empire State College. The results of this work reveal that student participation rates, quantity of student posts, quality of student posts and the extent of threading are well correlated with instructor activity.